Science and art the contemporary painted surface - Sgamellotti, Antonio (Royal Society of Chemistry, 2020)
Science and art are increasingly interconnected in the activities of the study and conservation of works of art. Science plays a key role in cultural heritage, from developing new analytical techniques for studying the art, to investigating new ways of preserving the materials for the future. Following on from the 2014 title "Science and Art: The Painted Surface", this book consists of a series of chapters written together by scientists, art historians, conservators, curators and artists dedicated to conservation, execution techniques, languages and conceptual topics. "Science and Art: The Contemporary Painted Surface" largely covers execution techniques, material's conservation and languages of artists, representative of twelve different countries, all protagonists of the development of innovative significant techniques and methodologies. 0The book opens with a focus on widely historicized artists, such as Jackson Pollock, Lucio Fontana, Enrico Baj, Piero Manzoni and Joseph Albers. Its core is dedicated to the work of major worldwide renowned living artists, in a perspective that, while considering the Sixties as the historical starting point of contemporaneity, does not neglect to offer a view on the work done in the immediately preceding years. Several interviews with artists are included. Final chapters are dedicated to contemporary design, net art, and painted surfaces in contemporary architecture
Keywords: Geschichte 1950-; Malerei; Kunstwerk; Konservierung; Restaurierung; Painting / Conservation and restoration; Painting / Expertising; Art and science; Aufsatzsammlung